Industri Pertahanan Prancis dan Inggris Dalam Penguatan Aliansi Kekuatan Militer pada Perang Dunia I - Dwi Soediantono; Amarulla Octavian (Department of History, Faculty of Humanities, Diponegoro University, 2021)
World War I took place on the European continent between the Allies and the Central powers. In this war, the warring parties did not only rely on the troops quantity, but also their own technology. In addition, both sides had maximally empowered their strategic industries in building military forces for war. The article identifies the factors that supported the victory of France and Britain in World War I, thus encouraging the development of war technology and strategic industry which continues to present day. In that arena, France and Britain had the upper hand in the use of technology and industrial support for war. The theories used for this discussion are Carl von Clausewitz's theory of war, Morgenthau's balance of power theory, Liddell Hart's strategy theory and the theory of revolution in military affairs. The discussion was carried out using qualitative methods with an exploratory and historical approach which ultimately showed that the Allied defense industry had so far gained technological advantage from the influence of the victory in World War I.